Analysis of Break Event Point in Optimizing Profit on The Mining Coal Company Listed in Indonesia Stock Exchange Period 2012-2016 - Wahyu Indah Mursalini (Jurnal Kajian Akuntansi dan Auditing, 2019)
The purpose of the company in running its business is to earn profit / profit. The size of the profits obtained often become a measure of success or failure of corporate management. In the profit planning relationship between cost, sales volume, and profit play a very important role. profit planning requires tools in the form of volume- profit cost analysis. One of the cost-volume-profit analysis techniques is break event point analysis. In general, this analysis also provides information about margin of safety that has usability as an indication and description to the management of how the sales decrease can be estimated so that the business run not suffer loss. So in a company should try as much as possible to avoid losses or even break-even. The purpose of this study is to determine the level of BEP achieved in optimizing earnings at coal mining companies listed on the Stock Exchange. The analytical method used is descriptive analysis. The results show that coal mining companies listed on the BEI have been able to optimize their performance so that it has obtained sales above the break event. A coal mining company should classify costs based on the cost behavior required to perform better profit planning for greater profits.